PENANGANGAN KONFLIK KOMUNAL MELALUI METODE KOMUNIKASI SOSIAL - Yusdarmoko, Sony; Putri, Rima Sari Indra (Jurnal Pertahanan dan Bela Negara, 2018)
Communal conflicts often occur in many areas in Indonesia. It disturbs and harms social security and harmony. In bigger escalation, it is a threat for national stability and coherence, as it may cause communal disintegration. Therefore, an active role of Indonesian Military Army (TNI) is needed to resolve conflict. The armyâ€™s role is in relation with its territorial command function, implemented in the method of Social Communication Territorial Command. This writing uses the Theory of Social Communication and The Lederach Theory of Conflict Transformation which divide conflict resolution in three levels of method and actor. By referring to Lederach, this writing proposes that the Social Communication Territorial Command will be effective in resolving conflict if it is focused in the optimalisation of the third level role as it is directly affecting wider society. To optimalizing their role, Babinsa, under the Command of Military should have knowledge of conflict resolution, and should possess good interpersonal and communication skills. In addition, there should be an adequate funding support to create social activities to enggange parties involved in conflict. Most importantly, the effort to resolve communal conflict should be done comprehensively by involving relevant parties and institution. Â Keywords: Communal Conflict, Social Communication, Territorial Command